Personality analysis of the main character Keke in film Surat Kecil Untuk Tuhan (Sigmund Freud’s psychoanalytic study) - Atya Reizkindra Amrilla, Atya; Raras Hafiidha Sari (Jurnal Disastri, 2023)
This research has a purpose in order to describe at a glance the Id (biological), Ego (psychological), and Super ego (sociological) in the film entitled Small Letters for God by using Sigmund Freud's Psychoanalytic theory. The focus of this research is how the Id, Ego, and Super ego reduce the personality of the main character in the film. Id, Freud also called the Id with System' der Unbewussten. This aspect is a biological aspect and is an outward or innate system found in all individuals. Ego, Freud also called the Ego with the System der Bewussten- Vorbewussten. This aspect is an aspect that is triggered by the need for organisms to correlate well with existing conditions and realities. Super ego, this aspect is a sociological aspect of personality. This study uses a qualitative descriptive method, based on language, phrases, words, and the like to become research data, in addition to the techniques used in producing this research data by means of observation and library techniques. Data analysis in this study was carried out by direct observation and deepening of the literature, by carrying out several stages, namely observing, marking, confirming data, and interpreting data, then analyze all data with Sigmund Freud's Psychoanalytic theory. The results of research on the film Small Letters for God can be concluded that the main character in this film has Id, Ego, and Super ego that are relevant to research.